Peran Pendidikan Karakter bagi Anak di Era Digital - Afri Nanda; Randa Gempa Saputra; Annisa Latifa (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Character education has an increasingly important role in facing the digital era that is full of challenges and temptations. This article discusses the role of character education in shaping children into moral individuals amidst the influence of technology and social media. We will explain the concept of character education, provide insights on how the digital era affects children's character development, and provide some strategies to integrate character education in education in the digital era.